Your original Eq is the Vertex form of a Y-Parabola that opens downward.
I am assuming you want to solve for X.
Standard form:
Y = -20/27(x^2 + 3x + 2.25)
Y = (-20/27)x^2 -(60/27)x - 5/3
Y = (-20/27)x^2 - (20/9)x - 5/3
Use Quadratic Formula.
X = -1.5, and -1.5(Double solution).
V(-1.5,0)
have got help from Damon on this question but all I need is help on integrating the answer he gave me into my original equation:
y=-15/20.25(x+1.5)^2+0
Here's Damon's help: (x+1.5)(x+1.5) = x^2 + 1.5 x + 1.5 x + (1.5*1.5)
= x^2 + 3 x + 2.25
So would I put this into my original quadratic equation?
Please and thank you as the help would be much appreciated!
1 answer